Analisis Kadar Eritrosit dan Hematokrit (HCT) pada Ibu Hamil untuk Membantu Diagnosis Anemia - Ni Luh Putu Yeyen Septiani (Universitas Pendidikan Ganesha, 2021)
This research is classified as descriptive research and aims to: (1) determine the levels of erythrocytes and hematocrit in pregnant women; and (2) determine the percentage of pregnant women who experience anemia from April 1 to May 31, 2008. The subjects of this study were the blood of pregnant women who checked themselves at the General Hospital Board (BRSU) Tabanan from April 1 to May 31, 2008. While the object of this study was the levels of erythrocytes and hematocrit in the blood of the pregnant women, Erythrocyte and hematocrit levels were determined using the hematology analyzer method. The results of this study indicated that (1) the levels of erythrocytes and hematocrit of pregnant women ranged from 2.0 to 4.56 million/L and 18 to 41.3%, and (2) the percentage who experienced anemia was 43.33%.